Women's perceptions about mobile health solutions for selection and use of family planning methods in Karachi: a feasibility study - Farina Gul Abrejo; Romaina Iqbal; Sarah Saleem (BMC, 2022)
Abstract Background The qualitative study explored the feasibility and acceptability of potential mHealth intervention for women living in low socio-economic areas to increase the uptake of family planning. The study also examined providers' perceptions' potential benefits of mHealth intervention. Methods The qualitative exploratory study recorded the perception of 23 women and conducted seven in-depth interviews with the providers of family planning services. These interviews assessed women's attitudes through; personal experience based on the usage of smartphones and family planning, acceptability for personal benefits, features of mobile applications and the convenient language, and self-efficacy for identifying the potential impact of mHealth intervention to increase women's empowerment for family planning usage. Results Three predetermined themes were used to record women's perceptions. Women's personal experience identified that women in low-socioeconomic areas use mobile phones frequently and also use them for gaining information related to health. Few women have experience using mobile phones to get information about sexual and reproductive health. Women considered; poor counselling and high transport costs to the facilities as significant barriers to getting family planning services. Perceived acceptability discussed the potential features of the mHealth app. Women considered that including short videos instead of written material would help them to understand its usage and complete information about family planning methods, including; dosage, expected side effects, and potential benefits suggested to include in the app. Women perceived that the mHealth intervention would save their transport costs to the facility and fill the information gap about family planning methods. In comparison, providers considered it would save time in counselling and motivating women at the facility. One of the significant factors discussed was self-efficacy in the form of women's empowerment in deciding on family planning. Women discussed that the mHealth intervention would increase their self-confidence to discuss the method with their husbands. Conclusion There is a high potential for mHealth interventions for family planning in Pakistan. The usage of mobile phones can increase women's acceptability and accessibility for family planning uptake in the country.